2015
DOI: 10.1002/mbo3.245
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of marine bacterial community diversity of the coastal waters of the reefs, inlets, and wastewater outfalls of southeast Florida

Abstract: Coastal waters adjacent to populated southeast Florida possess different habitats (reefs, oceanic inlets, sewage outfalls) that may affect the composition of their inherent microbiomes. To determine variation according to site, season, and depth, over the course of 1 year, we characterized the bacterioplankton communities within 38 nearshore seawater samples derived from the Florida Area Coastal Environment (FACE) water quality survey. Six distinct coastal locales were profiled – the Port Everglades and Hillsb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 117 publications
(144 reference statements)
17
60
0
Order By: Relevance
“…Although nutrient enrichment or pollution related factors were shown to be the only drivers of bacterial communities in coral reefs elsewhere [31,32,121,141], our results suggest that in less disturbed environmental settings, bacterial biofilms are influenced by a combination of temperature, salinity, DO, but also chlorophyll-a. Ex situ experiments confirmed a temperature induced regulation of bacterial biofilm composition and physiology [33,35,142].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although nutrient enrichment or pollution related factors were shown to be the only drivers of bacterial communities in coral reefs elsewhere [31,32,121,141], our results suggest that in less disturbed environmental settings, bacterial biofilms are influenced by a combination of temperature, salinity, DO, but also chlorophyll-a. Ex situ experiments confirmed a temperature induced regulation of bacterial biofilm composition and physiology [33,35,142].…”
Section: Discussionmentioning
confidence: 61%
“…Reef water bacterial community structure differed between seasons, but remained stable across reefs. This lack of spatial differences but strong seasonality may indicate minor land-based influences in our study area, given that reef water bacterial communities in areas of pollution are shown to change along spatial gradients and lack seasonal differences [121]. …”
Section: Discussionmentioning
confidence: 99%
“…The widespread abundance and dominance of the class Alphaproteobacteria on H. stipulacea along the gradient and at other meadows within the GoA (Weidner et al, 2000; Mejia et al, 2016) may be due to its natural abundance in the water column and its capability to thrive in multiple environmental conditions, especially in oligotrophic coastal waters (Dang et al, 2008; Witt et al, 2012; Elifantz et al, 2013). In particular, the family Rhodobacteraceae has been significantly linked with variations in water column salinity, oxygen saturation, pH, nitrate concentration, and temperature (Buchan et al, 2005; Campbell et al, 2015b). In sediments, multiple factors can influence the bacterial community structure of seagrass rhizomes and roots.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities, due to their capability to rapidly shift in structure and function as a response to environmental change, may influence the health of their hosts (Zilber-Rosenberg and Rosenberg, 2008) by several means such as providing protection against pathogens (Rosenberg et al, 2007; Taylor et al, 2007), nitrogen fixation (Singh et al, 2004), and securing nutrient availability (Rout et al, 2013; Coats and Rumpho, 2014). In the same way, host condition (Marzinelli et al, 2015), rather than just environmental variables (Campbell et al, 2015a,b), may determine the structure of the closely associated microbial communities. Simultaneous assessments of seagrass ecophysiology and microbial community structure are therefore important to understand the capacity of the holobiont to persist under changing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The major source of faecal pollution to the coastal marine environment varies depending upon the surface currents, with both inlets and ocean outfall surface boils having tested positive for human and zoonotic pathogens (e.g. Furthermore, inlet waters have previously been identified as a source of faecal pollution at local beaches because they receive agricultural/cattle and storm water runoff as well as untreated domestic wastewater from leaky septic systems abutting waterways (Meeroff et al 2008;Futch et al 2011;Carsey et al 2012;Campbell et al 2015). ; Rosario et al 2009;Bloetscher et al 2011;Futch et al 2011;Bloetscher et al 2014).…”
Section: Introductionmentioning
confidence: 99%